O DIREITO À EDUCAÇÃO E O ATIVISMO JUDICIAL NA PERSPECTIVA DA DECISÃO DO SUPREMO TRIBUNAL FEDERAL - Galbiati, Carolina Maria Morro Gomes (Revista da AJURIS, 2012)
THE RIGHT TO EDUCATION AND THE JUDICIAL ACTIVISM ON THE PERSPECTIVE OF THE DECISION OF THE FEDERAL SUPREME COURT RESUMO: A Constituição Federal de 1988 reconheceu o direito à educação em seu art. 205 como direito de todos e dever do Estado, da família e da sociedade. Observa-se que a educação básica constitui direito público subjetivo e compreende aquela prestada dos quatro aos dezessete anos de idade. Eis o caráter que lhe conferiu a Constituição Federal de 1988 – direito social e fundamental. Em se tratando, pois, de direito social, a sua efetividade deve ser assegurada pelo Estado por meio da implantação de políticas públicas destinadas ao campo específico da educação básica. Ademais, verifica-se que o cidadão é titular deste direito fundamental e detém o poder de exigir tal prestação inserida em sua esfera de direitos. No entanto, enfatiza-se que, em recente decisão, o Supremo Tribunal Federal atribuiu efetividade plena ao art. 208, IV, da Constituição Federal de 1988, na redação dada pela Emenda Constitucional nº 53/2006, que trata da educação infantil, corroborando a adoção da postura do ativismo judicial. Considerados esses aspectos, o presente artigo pretende analisar a decisão proferida pelo Supremo Tribunal Federal no Agravo Regimental no Recurso Extraordinário nº 639.337 do Estado de São Paulo. Para tanto, inicialmente, o estudo tratará do direito à educação no contexto da Constituição Federal de 1988. Segue-se a abordagem ao ativismo judicial, para, por fim, analisar a decisão do STF no âmbito do agravo regimental do recurso extraordinário mencionado, como possível ocorrência do ativismo judicial. PALAVRAS-CHAVE: Direito à educação; Constituição Federal/1988; ativismo judicial; decisão judicial. ABSTRACT: The Federal Constitution of 1988 recognized the right to Education in the article 205 as due to anyone and a duty of the State, the family and society. It is observed that a basic education constitutes a subjective public right and comprehends that provided for children between the ages of about four and seventeen years old. Here it is the character conferred on basic education by the Federal Constitution of 1988 – it is a social and fundamental right. As a result of being a social right, its fulfillment must be instituted by the State through the establishment of public policies aimed at the specific field of basic education. Besides being entitled to have this fundamental right, the citizen holds the power to demand for such a provision which is inserted into his table of constitutional rights. However, it must be emphasized that in a recent decision the Federal Supreme Court attributed fully effectivity to article 208, IV, of the Federal Constitution of 1988 in the writing put down through Constitucional Amendment nº 53/2006, which deals with childhood education, corroborating to strengthen the adoption of a posture that approaches to judicial activism. Considering these aspects, the present article intends to analyze the decison pronounced by the Federal Supreme Court in the Regimental Grievance in the Extraordinary Appeal nº 639.337 of the State of São Paulo. For that purpose, firstly the study deals with the right to Education within the context of the Federal Constitution of 1988, then considers the judicial activism, and finally approaches the decision emanated from Federal Supreme Court, correlating the content of the Regimental Grievance in the above-mentioned Extraordinary Appeal with the possible occurrence of judicial activism. KEYWORDS: The right to education; Federal Constitution/1988; judicial activism; judicial decision. SUMÁRIO: Introdução; 1 Direito à educação no contexto da Constituição Federal de 1988; 2 Ativismo judicial; 3 Análise da decisão do Supremo Tribunal Federal no Agravo Regimental em Recurso Extraordinário nº 639.337 do Estado de São Paulo; Considerações finais; Referências. SUMMARY: Introduction; 1 The right to education within the context of the Federal Constitution of 1988; 2 Judicial activism; 3 Decision analysis by the Federal Supreme Court in the Regimental Grievance in the Extraordinary Appel nº 639.337 of the State of São Paulo; Last considerations; References.